2013
DOI: 10.1175/jcli-d-12-00554.1
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-First-Century Compatible CO2 Emissions and Airborne Fraction Simulated by CMIP5 Earth System Models under Four Representative Concentration Pathways

Abstract: The carbon cycle is a crucial Earth system component affecting climate and atmospheric composition. The response of natural carbon uptake to CO 2 and climate change will determine anthropogenic emissions compatible with a target CO 2 pathway. For phase 5 of the Coupled Model Intercomparison Project (CMIP5), four future representative concentration pathways (RCPs) have been generated by integrated assessment models (IAMs) and used as scenarios by state-of-the-art climate models, enabling quantification of compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
259
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 281 publications
(283 citation statements)
references
References 26 publications
17
259
1
2
Order By: Relevance
“…CESM includes nitrogen limitation of gross primary production and thus has a weaker response of photosynthesis to CO 2 fertilization and less uptake of CO 2 in natural lands as compared with other CMIP5 models [Arora et al, 2013;Jones et al, 2013;Thornton et al, 2009] and some observations [Friedlingstein and Prentice, 2010]. The relatively low sensitivity of CESM to rising CO 2 suggests that our calculations may underestimate the indirect carbon fluxes associated with LULCC.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…CESM includes nitrogen limitation of gross primary production and thus has a weaker response of photosynthesis to CO 2 fertilization and less uptake of CO 2 in natural lands as compared with other CMIP5 models [Arora et al, 2013;Jones et al, 2013;Thornton et al, 2009] and some observations [Friedlingstein and Prentice, 2010]. The relatively low sensitivity of CESM to rising CO 2 suggests that our calculations may underestimate the indirect carbon fluxes associated with LULCC.…”
Section: Resultsmentioning
confidence: 91%
“…This is consistent with the higher amplification factors deduced in simulations extending to 2100 as reported in Gitz and Ciais [2003] for different land use scenarios using a model with a stronger response of photosynthesis to CO 2 fertilization. On the other hand, the CESM model tends to have a lower temperature sensitivity of land and ocean carbon uptake [Arora et al, 2013;Jones et al, 2013] and thus may lose less carbon due to temperature increases, especially after 2100. Because the physical parameterizations of the Earth system model and the land use scenario Global Biogeochemical Cycles 10.1002/2016GB005374 are important to the impact of LULCC and the calculation of AF, calculating these values across multiple models provide one means to assess the robustness of these results.…”
Section: Resultsmentioning
confidence: 99%
“…ESMs simulate the compatible net CO 2 emissions based on mass balance between atmospheric changes in CO 2 and land and ocean carbon sinks. A model intercomparison of ten ESMs found that two-thirds of the models required net negative emissions in the second half of the century 9 , but the ESMs make no assumption on how this is technically achieved. For IAMs, negative emissions are an outcome of an economic optimization driven by a choice between reducing emissions and BECCS (gross negative emissions).…”
Section: Opinion and Commentmentioning
confidence: 99%
“…This area would need to increase by over 1,000 Mha to feed 9 billion people 53 under current trends of intensification and extensification, occupying together with current pastures close to 50% of all lands. Three of the four new IPCC scenarios (RCPs) require increased cropland area to feed the world population by 2100 at the expenses of forests and available pasture land (the latter due to the intensification of the livestock sector) 54 .…”
Section: Nature Communications | Doimentioning
confidence: 99%